Self-Employment in Chile, Long Run Trends and Education and Age Structures Changes - Puentes, Esteban (Estudios de Economía, 2016)
This paper studies long-term trends of self-employment in Chile. Self-employmentis associated with poor job conditions, vulnerability, and instability or informallabor market. Contrary to what is expected, self- employment level does notrespond to macroeconomic variables. Using forty-one cross sections of thelongest Employment Survey available, we show that there is little correlation ofthe economic cycle with variations in self-employment. Cohort effects are alsounimportant. In fact, age is the most important predictor of self- employment;older people are more likely to be self-employed. In addition, we performed adecomposition of changes in self-employment on changes in coefficients, whichare a measure of the returns to individual characteristics, and on changes incharacteristics. The results indicate that self-employment should have decreasedgiven the changes in individual characteristics, but was prevented by changes incoefficients. We also find indirect evidence that these changes in parameters arenot correlated with macroeconomic variables. Finally, the changes in individualcharacteristics, such as education and age, and changes in their coefficientsaccount for most of the changes in self-employment.